2003
DOI: 10.1093/gerona/58.9.m851
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-Converting Enzyme Gene Polymorphism in Two Ethnic Groups Living in Brazil's Southern Region: Association With Age

Abstract: We cannot dismiss the possibility of the association between ACE polymorphism and age involving linkage disequilibrium, since the nature of this phenomenon is still controversial. From our studies, it appears that there is a correlation between age, ethnicity, and ACE polymorphism. More of such studies are warranted, as further investigation in this area will have a high clinical relevance to cardiovascular disease and aging research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…The first phase of the project included several investigations in a free-living elderly community (≥ 60 years old) between 2000 and 2006, including associations between gene polymorphism and several risk factors for chronic diseases 13,14 and smoking addiction. 15 This study will be combined with future complementary investigations using genetic approaches, and therefore all the subjects included were Caucasian, given that the State of Rio Grande do Sul in Brazil has higher prevalence of this ethnic group than of other groups due to the massive European colonization.…”
Section: Methodsmentioning
confidence: 99%
“…The first phase of the project included several investigations in a free-living elderly community (≥ 60 years old) between 2000 and 2006, including associations between gene polymorphism and several risk factors for chronic diseases 13,14 and smoking addiction. 15 This study will be combined with future complementary investigations using genetic approaches, and therefore all the subjects included were Caucasian, given that the State of Rio Grande do Sul in Brazil has higher prevalence of this ethnic group than of other groups due to the massive European colonization.…”
Section: Methodsmentioning
confidence: 99%
“…Control individuals were recruited from an existing database of 746 socially active healthy subjects who took part in a community-based research named GENESIS Program that investigates genetic-environmental interactions on human ageing [18,19]. This investigation was structured considering the checklist for reporting and appraising of genediseases associations proposed by Little et al [20].…”
Section: Study Participantsmentioning
confidence: 99%
“…Ancestry of the southern region of Brazil has great ethnic variation, which is highlighted in major urban areas, such as the metropolitan region of Greater Porto Alegre, which does not present any significant ethnic isolation (17,18). A study conducted by Da Cruz and colleagues (19) showed that the ethnic composition of the metropolitan region of Greater Porto Alegre is appropriate for the implementation of epidemiological studies on aging. Thus, we opted for considering the two sources of the sample as being one single population genetically.…”
Section: Methodsmentioning
confidence: 99%